PEMANFAATAN LIMBAH HASIL PEMBUATAN ANYAMAN BERBAHAN BAMBU SEBAGAI CAMPURAN STANDARD MIXDESIGN PAVING BLOCK - Amanda Rizky Fauzy; Arthur Daniel Limantara; Yosef Cahyo Setianto Purnomo (Kadiri University, 2018)
Exploitation of stone use as the main component of concrete needs to be reduced. The presence of alternative rough aggregate substitute in concrete mixture needs to be applied. This research aims for the optimum percentage of the percentage of value of the addition of waste fibre woven bamboo to achieve a strong press of minimum and magnitude of absorption percentage. This research was conducted in Civil Engineering Laboratory of Kadiri University using trial and error method, sample used in cube dimension 15 x 15 x 15 cm with 20 pieces with planned quality K-225 or 18.675 MPa. Comparison of percentage of based on rough aggregate volumes on the mix of paving blocks. Compessive strength test at 28 days. The results showed Compessive strength on the bamboo fiber variation 0%, 5%, 15% and 25% for 20.7 MPa, 17.6 MPa, 12.3 MPa and 9.9 MPa obtained the optimum fibre woven bamboo percentage of in accordance with minimum limit of strong standard press paving block 17 MPa by 7%. The absorption test results showed an increase that was directly proportional to the percentage of the variation of the addition with an average of 0.1%, 0.1%, 0.2% and 0.3%, with optimal absorption of 0.103%.Eksploitasi penggunaan batu sebagai komponen utama beton perlu direduksi. Adanya alternatif pengganti agregat kasar dalam campuran beton perlu diterapkan. Penelitian ini dilakukan untuk mencari nilai prosentase optimum penambahan serat limbah anyaman bambu agar mencapai kuat tekan minimal serta besarnya prosentase penyerapan. Penelitian ini dilakukan di Laboratorium Teknik Sipil Universitas Kadiri menggunakan metode trial and error, sample yang digunakan berbentuk kubus dimensi 15 x 15 x 15 cm sebanyak 20 buah dengan mutu yang direncanakan K-225 atau 18,675 MPa. Perbandingan prosentase subtitusi berdasarkan volume agregat kasar pada campuran paving block. Pengujian kuat tekan dilakukan pada umur 28 hari. Hasil pengujian menunjukkan kuat tekan rata-rata pada variasi serat bambu 0%, 5%, 15% dan 25% sebesar 20,7 MPa, 17,6 MPa, 12,3 MPa dan 9,9 MPa sehingga didapatkan prosentase serat limbah anyaman bambu optimum sesuai batas minimal standar kuat tekan paving block 17 MPa sebesar 7%. Hasil uji absorpsi menunjukkan peningkatan yang berbanding lurus dengan prosentase variasi penambahan dengan rata-rata sebesar 0,1%, 0,1%, 0,2% dan 0,3%, dengan penyerapan optimum sebesar 0,103%.